2017
DOI: 10.1515/pac-2016-1113
|View full text |Cite
|
Sign up to set email alerts
|

Electroflotation extraction of sparingly soluble compounds of non-ferrous and rare-earth metals from liquid technological waste

Abstract: The experimental results describing electroflotation extraction process are presented and analyzed for sparingly soluble compounds of non-ferrous and rare-earth metals, the influence of the disperse phase particle size and particle surface charge on the efficiency and electroflotation rate having been determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Electrochemical technologies are widely used in the field of wastewater treatment and processing of technological solutions containing both inorganic [1][2][3][4][5][6][7][8][9][10][11]35] and organic [1,6,[12][13][14][15][16][17][18][19][20][21][22] pollutants. Electroflotation and electrocoagulation can be efficiently used not only in sewage treatment ISSN 2224-5278 with removal and destruction of pollutants, but also for separation of rare and scarce elements from aqueous solutions [6,10,23]. It seems promising to convert ions of scarce elements to the form of insoluble compounds, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical technologies are widely used in the field of wastewater treatment and processing of technological solutions containing both inorganic [1][2][3][4][5][6][7][8][9][10][11]35] and organic [1,6,[12][13][14][15][16][17][18][19][20][21][22] pollutants. Electroflotation and electrocoagulation can be efficiently used not only in sewage treatment ISSN 2224-5278 with removal and destruction of pollutants, but also for separation of rare and scarce elements from aqueous solutions [6,10,23]. It seems promising to convert ions of scarce elements to the form of insoluble compounds, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…All non-ferrous heavy and rare earth metals and their compounds are toxic. The Studies conducted on the electroflotation of metal oxides and hydroxides [8,9] showed that the process is most efficient for particles of a dispersed phase with sizes from 10 to 100 microns, having a small positive or zero charge (ζ-potential equal to 0...+5 mV). With strongly negatively charged particles the process is less efficient.…”
mentioning
confidence: 99%